Analysis Of The Implementation Of Internal Audit, Risk Management, And Customer Eligibility In Minimizing Problems In Financing Risks At Bank Sumut Syariah Kcp Kisaran - Alfarezzi, Ahmad; Sugianto, Sugianto; Anggraini, Tuti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This study aims to determine "Analysis of the Application of Internal Audit, Application of Manajemen Resiko and Analysis of Customer Feasibility in Minimizing the Risk of Problematic Financing at Bank Sumut Syariah KCP Range". This research was conducted at Bank Sumut Syariah KCP Kisaran. The method in this study uses qualitative methods in the form of data research (field research). The results of this study are that Bank Sumut Syariah KCP Kisaran has implemented risk management through internal audits, the implementation of risk management by Bank SUmut Syariah KCP Kisaran covers all activities in the bank and the feasibility analysis of customers used at Bank Sumut Syariah using the 5C principle.